2022
DOI: 10.1038/s41598-022-11123-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of experimental colitis on mitochondrial bioenergetics in intestinal epithelial cells

Abstract: Intestinal homeostasis is highly dependent on optimal epithelial barrier function and permeability. Intestinal epithelial cells (IEC) regulate these properties acting as cellular gatekeepers by selectively absorbing nutrients and controlling the passage of luminal bacteria. These functions are energy demanding processes that are presumably met through mitochondrial-based processes. Routine methods for examining IEC mitochondrial function remain sparse, hence, our objective is to present standardized methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Additionally, during the ultrastructural examination, we observed common mitochondrial swelling in intestinal epithelial cells following DSS-induced inflammation, particularly in the context of alk-SMase deletion, indicating more pronounced mitochondrial degeneration. DSS-induced murine colitis has been previously reported to affect mitochondrial function, resulting in reduced intestinal barrier function and increased permeability[ 38 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, during the ultrastructural examination, we observed common mitochondrial swelling in intestinal epithelial cells following DSS-induced inflammation, particularly in the context of alk-SMase deletion, indicating more pronounced mitochondrial degeneration. DSS-induced murine colitis has been previously reported to affect mitochondrial function, resulting in reduced intestinal barrier function and increased permeability[ 38 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all the 13mitochondria-encoded genes were found to be related to ATP production. Interestingly, using colonic biopsies from ulcerative colitis patients, Sünderhauf and collaborators [65] demonstrated that mucosal energy deficiency is linked to impaired goblet cell differentiation, thus pointing out an impaired production and secretion of mucin-producing goblet cells in ulcerative colitis.…”
Section: Alterations Of Energy Metabolism In Inflammatory Bowel Diseasesmentioning
confidence: 99%
“… Timing: 60 min Prepare mitochondrial respiration MiR05 1 solution following materials and equipment section. Calibrate the respirometry following Oxygraph-2k respirometer 1 , 2 user manual for specific procedures. Note: Calibration of the Oxygraph is an essential step to minimize confounding effects of instrumental oxygen consumption.…”
Section: Before You Beginmentioning
confidence: 99%
“…Calibrate the respirometry following Oxygraph-2k respirometer 1 , 2 user manual for specific procedures.…”
Section: Before You Beginmentioning
confidence: 99%
See 1 more Smart Citation